Pengembangan Teknologi Investment Casting Untuk Pembuatan Produk Cor Substitusi Impor Dengan Pemanfaatan Bahan Baku Lokal - Hafid Abdullah; Sri Bimo Pratomo (Jurnal Metalurgi dan Material Indonesia, 2019)
The development of investment casting technology for the manufacture of import substitution casting products by using of local raw materials has been done. Compared to the conventional casting process, investment casting has the advantage of being able to create a complex casting product and produce a product that is near net shape so that it is no need machining process. The objective is as an effort to find an alternative method of making a quality casting product, has high added value with the utilization of local raw materials available in Indonesia so as to reduce the cost of production and dependence on imports of industrial raw materials which are very expensive in the investment casting process. The method of making casting products with investment casting process, including: pattern making, mould making, dewaxing, melting, pouring, finishing and testing. Investment casting technology has been successfully applied to the manufacture of rocker arm, impeller pump and turbine blade with the utilization of local raw materials ie: epoxy resin as a substitute for metal pattern, mixture wax of paraffin and celo resin for the pattern of wax and zircon sand of Bangka as coating slurry for ceramic mould. The discussion of this paper is expected to be a case of developing other casting products needed by Indonesia for industry: medical equipment, agricultural equipment, textile equipment, gun and small armaments, electronics, automotive and electrical components etc.